Investigating the endocrine disruption effects of four disinfection byproducts on zebrafish estrogen receptor-α - Lee, Sang-Ah; Ryu, Chang Seon; Park, Chang Gyun; Cho, Hyunki; Jun, Indong; Park, Chang-Beom; Esterhuizen, Maranda; Kim, Young Jun (Frontiers in Marine Science, 2023)
Reports have shown an increase in the use of disinfectants in wastewater treatment plants, prompted by the detection of residual viruses in sewage. However, the release of disinfection byproducts (DBPs) in final effluents has raised concerns about their potential adverse effects, such as endocrine disruption, on aquatic environments. Despite these concerns, few studies have examined the endocrine-disrupting effects of DBPs on fish, which may be vulnerable to DBPs. The aim of this case study was to investigate the endocrine-disrupting properties of four commonly formed DBPs: chloroiodomethane (CIM), dibromochloromethane (DBCM), bromodichloromethane (BDCM), and trichloroacetic acid (TCA) on the estrogen receptor-α in zebrafish (zERα). The results indicated that all four DBPs have high anti-estrogenic activity against zERα; with CIM, BDCM, DBCM, and TCA yielding 80.8%, 78.4%, 49.0%, and 64.1% anti-estrogenic effects on zERα, respectively. Moreover, all DBPs demonstrated negligible estrogenic effects on zERα. Our study sheds new light on the adverse effects of DBPs, particularly the endocrine-disrupting activity of CIM, which, as part of the dihalomethanes group, has received limited research attention in the past. This study shows the molecular interactions in terms of the endocrine disruption of DBP on zERα, warranting further studies to understand the overall impact of fish in affected aquatic ecosystems.